2006
DOI: 10.1136/pgmj.2005.036483
|View full text |Cite
|
Sign up to set email alerts
|

Acquired haemophilia heralded by bleeding into the oral mucosa in a patient with bullous pemphigoid, rheumatoid arthritis, and vitiligo

Abstract: Acquired haemophilia is rare and potentially fatal, with a mortality of 20% if left untreated. There is a strong association with other autoimmune diseases. This report describes a patient with rheumatoid arthritis, vitiligo, and bullous pemphigoid where the diagnosis of acquired haemophilia was made after an extensive bleed into a bullous lesion in the buccal mucosa. This case highlights some of the potential complications of acquired haemophilia and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
(5 reference statements)
1
19
0
Order By: Relevance
“…Presenting symptoms of BP associated AH include hematomas, ecchymosis, gastrointestinal bleeding and oral mucosal bleeding. This was compatible with the history of lip hematoma in our patient [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 89%
“…Presenting symptoms of BP associated AH include hematomas, ecchymosis, gastrointestinal bleeding and oral mucosal bleeding. This was compatible with the history of lip hematoma in our patient [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 89%
“…This should be revealed through the course of a detailed medical history and examination. Reported associations include systemic lupus erythematosus, rheumatoid arthritis, multiple sclerosis, Sjögren syndrome and Myasthenia gravis which was of relevance in this case. The dental clinician in particular should make careful note of oral and dermatological manifestations of autoimmunity including psoriasis, epidemolysis bullosa, pemphigus and bullous pemphigoid …”
Section: Discussionmentioning
confidence: 78%
“…The dental clinician in particular should make careful note of oral and dermatological manifestations of autoimmunity including psoriasis, epidemolysis bullosa, pemphigus and bullous pemphigoid. 19 Bleeding can be iatrogenic or induced by minor trauma. This is of particular relevance following invasive oral surgery procedures that produce intra-oral wounds with bone exposure in highly vascular areas.…”
Section: Discussionmentioning
confidence: 99%
“…2,19,[25][26][27][28] It is also reported that 2-8.3% of AH cases are associated with skin disorders: these include psoriasis vulgaris, bullous pemphigoid, exfoliative dermatitis, pemphigus vulgaris, erythema multiforme, erythema annulare centrifugum, scleroderma, malignant melanoma and nonspecific dermatoses. 2,6,7,19,25,26,29,30 Reported cases of autoimmune bullous dermatoses associated with AH include pemphigus vulgaris, [31][32][33] pemphigus erythematosus, 34 bullous pemphigoid, [35][36][37][38][39][40][41][42][43][44] epidermolysis bullosa acquisita [45][46][47] and anti-laminin 5 pemphigoid. 48 However, to the best of our knowledge, there have not been any previous reports of LABD associated with AH, so the present report may be the first case of LABD associated with AH.…”
Section: Discussionmentioning
confidence: 99%